PENGARUH KUALITAS PELAYANAN, STRATEGI PEMASARAN DAN FASILITAS TERHADAP KEPUASAN TAMU DI HOTEL GRAN PURI MANADO - Sony Wijanarko; Helni Desty Yanice Lagarense; Meylita Laikun; Tesalonika Kaunang (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
This study aims to examine the effect of service quality, marketing strategy, and facilities on guest satisfaction at Hotel Gran Puri Manado. The research employed a quantitative approach using a survey method, with data collected from 30 hotel guests as respondents. Data were obtained through a structured questionnaire measuring guests’ perceptions of service quality, marketing strategy, and facilities in relation to their overall satisfaction. The data were analyzed using multiple linear regression analysis. The results indicate that service quality, marketing strategy, and facilities have a significant effect on guest satisfaction at Hotel Gran Puri Manado. Among these variables, marketing strategy and facilities emerge as dominant factors influencing guest satisfaction. The findings of this study provide practical implications for hotel management, emphasizing that continuous improvement in service quality, effective marketing strategies, and adequate facilities is essential to enhance guest satisfaction and maintain competitiveness in the hospitality industry.